Genetic Diversity Analysis of Eighteen Tea (Camellia sinensis L.) Clones of Bangladesh Through RAPD - Boonerjee, Shefali; Islam, M. Nurul; Hoque, M. I.; Sarker, R. H. (Plant Tissue Culture and Biotechnology, 2014)
Using 20 decamer random primers molecular characterization of 18 tea (Camellia sinensis L.) clones of Bangladesh was made. All the primers showed significant amplification in PCR analysis. A total of 755 bands was produced in all the 18 tea clones with an average of 37.75 RAPD bands per primer. Among all the bands 97.41% were polymorphic in nature. The molecular size of the amplified DNA fragments ranged from 250 to 5000 bp. Ten unique bands were amplified from the genome of the 18 tea clones. The values of pairwise genetic distance ranged from 24.0 to 59.0 indicating the presence of a wide range of genetic diversity. The highest genetic distance 59 was found between the clone BT16 and BT2, whereas the lowest (24.0) between BT18 and BT5. The dendrogram based on Neis genetic distance was constructed using un-weighted Pair Group of Arithmetic Mean (UPGMA) segregating the 18 tea clones into two major clusters: BT9 and BT13 in cluster 1 and the remainder of 16 clones in cluster 2. Cluster 2 is further sub-divided into many sub-clusters. Cluster analysis revealed that while the genotype BT5 is closely related to BT18, BT1 and BT2 showed similarity with BT8. Genotypes BT1 and BT13 were widely diverse genetically. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.175010 Plant Tissue Cult. & Biotech. 23(2): 189-199, 2013 (December)